PENGARUH FOOD QUALITY, SERVICE QUALITY, DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PADA MCDONALD’S DI KOTA KENDARI - Revi Julianingsih; Patwayati; Nursaban Rommy; Endro Sukotjo; Riski Amalia Madi; Nurul Ittaqullah (Jurusan Manajemen FEB UHO, 2024)
This research aims to determine the influence of food quality, Service Quality, and Brand image on McDonald's purchasing decisions, to determine the influence of food quality on Mcdonald's purchasing decisions, to determine the influence of Service Quality on Mcdonald's purchasing decisions, to determine the influence of Brand image on Mcdonald's Kendari purchasing decisions. The sampling technique in this research is the Incidental Sampling and Purposive Sampling methods. The total sample in this study was 96 respondents who were Mcdonald's consumers in the city of Kendari. The data analysis used is descriptive analysis and multiple linear regression analysis using SPSS software. Based on the research results that the food quality, Service Quality and Brand image variables together or simultaneously have a positive and significant influence on McDonald's purchasing decisions, the food quality variable partially does not have a positive and significant influence on the decision to return McDonald's products. Furthermore, the Service Quality variable partially has a positive and significant influence on the decision to return McDonald's products and the Brand image variable partially has a positive and significant influence on the decision to return McDonald's products.